Media programs : district and school - 4 0 16; 5 Association for Educational Communications and Technology.;American Library Association.;American Association of School Librarians (Chicago : American Library Association, 1975)
Delineates guidelines and recommendations for media programs and resources essential for quality education.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Media programs (Education);School libraries.;Instructional materials centers.;School libraries; 20; 2